2022
DOI: 10.3390/children9050745
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Youth with Chronic Pain and Their Parents: A Longitudinal Examination of Who Are Most at Risk

Abstract: Objectives: Chronic pain and mental illness in youth and parents are poised to reach new heights amidst the societal and healthcare impacts of the COVID-19 pandemic. Evidence from natural disasters (i.e., hurricanes) suggests that a degree of personal impact and individual personality may moderate the effects of high stress events, such as the COVID-19 pandemic, on mental health. Methods: In a pre-existing cohort of 84 youth with chronic pain (Mage = 14.39; 12–18 years; 67.8% female) and 90 parents (86.7% fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Youth expressed changes in pain symptoms and mental health challenges, which subsequently impacted their caregivers and siblings, resulting in changes to family dynamics. Some quantitative studies among youth with chronic pain reported no change 29 or reductions in pain symptoms during the pandemic 21 ; however, many studies found increases in mental health challenges. 21 , 29 , 48 Our research team completed a large survey-based study with over 600 youth, siblings, and parents and found significant increases in mental health symptoms such as anxiety, depression, and PTSD; however, significant changes in pain intensity were not found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Youth expressed changes in pain symptoms and mental health challenges, which subsequently impacted their caregivers and siblings, resulting in changes to family dynamics. Some quantitative studies among youth with chronic pain reported no change 29 or reductions in pain symptoms during the pandemic 21 ; however, many studies found increases in mental health challenges. 21 , 29 , 48 Our research team completed a large survey-based study with over 600 youth, siblings, and parents and found significant increases in mental health symptoms such as anxiety, depression, and PTSD; however, significant changes in pain intensity were not found.…”
Section: Discussionmentioning
confidence: 99%
“…Some quantitative studies among youth with chronic pain reported no change 29 or reductions in pain symptoms during the pandemic 21 ; however, many studies found increases in mental health challenges. 21 , 29 , 48 Our research team completed a large survey-based study with over 600 youth, siblings, and parents and found significant increases in mental health symptoms such as anxiety, depression, and PTSD; however, significant changes in pain intensity were not found. 37 In contrast, most qualitative studies among youth and adults with chronic pain recounted a deterioration of their pain condition during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study did not focus on the impact of the pandemic on mental health in youth specifically, it is possible that this contextual factor might in part explain the higher rates of mental health symptoms in this sample, consistent with previous research noting high rates of mental health concerns in youth during this period. 7…”
Section: Discussionmentioning
confidence: 99%